APPLICATION OF DEDUCTIVE METHOD IN NAHWU MATNU LEARNING AL-JURUMIYAH STUDENTS OF CLASS X NURUL HADID PUTRI KUNINGAN BOARDING SCHOOL - Fajriyah, Nabila Nur (Al-Mubin, 2025)
This study aims to analyze the application of the deductive method in teaching Nahwu using the Matnu Al-Jurumiyah text in the 10th grade at Nurul Hadid Islamic Boarding School, Kuningan, academic year 2024–2025. The research focuses on instructional effectiveness and the factors influencing the selection of teaching methods. Using a qualitative approach with Classroom Action Research (CAR), 14 female students were involved. Data were collected through observation, interviews, documentation, and literature review. The findings indicate that the deductive method effectively introduces basic grammar rules in Nahwu. However, variations in students' understanding suggest the need for more flexible strategies. While the deductive approach is suitable as a foundation, it should be complemented with other methods in advanced levels to maximize learning outcomes